Kinematics of a combined modular dynamic simulator - Яглінський, Віктор Петрович; Обайді, Аймен Сабах (Technology audit and production reserves, 2014)
Developing the methods and systems for reproducing accelerative sensations of vehicle operator when performing emergency maneuvering is an actual scientific and practical problem. The aim of the research is to create a dynamic model of the combined modular simulator for ensuring linear and angular velocities and accelerations during drift, pitch and instant emergence of obstructions. The combined simulator with linear motors of basis, on which the hexapod-type parallel structure mechanism with rods of variable length is installed, is proposed. Using mathematical models of kinematics and dynamics of industrial platforms, worked through by the authors on the standard samples of engineering products, has allowed to create the calculated dependences for modeling the level of overload on the vehicle operator. A method for determining the parameters of the working motion and assessing the capacity of the drive and individual drive units when practicing the specified maneuver by the simulator is proposed. On the example of reproducing the "pitch" type maneuver by the simulator, modeling specific accelerative information of the vehicle operator in the wide range of accelerations when passing the path at different speeds for different time intervals is demonstrated. The research results can be used in training operators of vehicles how to drive and act when taking off, speeding up, braking and overcoming the obstacles such as ramps, lifts, hillsides.